Data on exercise and cardiac imaging in a patient cohort with hypertrophic cardiomyopathy - Dejgaard, Lars A. (Data Brief, 2017)
Data presented in this paper are supplementary material to our study “Vigorous exercise in patients with hypertrophic cardiomyopathy” [1]. The current article presents supplementary data on collection and analyses of exercise parameters and genetic data in the original research article.